Epidemiology of injuries in National Collegiate Athletic Association men's basketball: 2014-2015 through 2018-2019 - Morris, S. N.; Chandran, A.; Lempke, L. B.; Boltz, A. J.; Robison, H. J.; Collins, C. L. (Journal of Athletic Training, 2021)
Context: Basketball has remained a popular sport for players and spectators in the United States since before the first National Collegiate Athletic Association men's championship tournament in 1939. Background: Routine examinations of men's basketball injuries are important for identifying emerging temporal patterns. Methods: Exposure and injury data collected in the National Collegiate Athletic Association Injury Surveillance Program during 2014-2015 through 2018-2019 athletic seasons were analyzed. Injury counts, rates, and proportions were used to describe injury characteristics, and injury rate ratios were used to examine differences in injury rates. Results: The overall injury rate was 7.28 per 1000 athlete exposures, with competition rates twice those of practices (injury rate ratio = 2.07; 95% CI = 1.93, 2.22). Injuries to the ankle (22.2%), knee (13.0%), head/face (11.3%), and hand/wrist (10.1%) accounted for most reported injuries, with sprains (30.4%), contusions (14.3%), and strains (13.9%) most commonly reported. Ankle sprain rates initially trended upward and decreased between 2017-2018 and 2018-2019; concussion rates remained relatively stable during 2014-2015 through 2018-2019. Conclusions: Findings suggest that common injury rates are trending downward relative to previous study findings.